Cognitive Distortions of Child Molesters on Probation or Parole in Japan12. (5th February 2016) - Katsuta, Satoshi; Hazama, Kyoko
Abstract: The present study examined cognitive distortions of child molesters on probation or parole in Japan utilizing an 18‐item questionnaire administered in a treatment program conducted by the probation officers. This study analyzed the responses of child molesters ( n = 51), non‐child‐molesting sexual offenders ( n = 65), and non‐offenders ( n = 64). Factor analysis of the responses showed three types of cognitive distortions: Rationalization of Offending Behavior, Minimization of Responsibility for Offending, and Minimization of Victim Harm. Welch's analysis of variance followed by Games‐Howell post hoc tests revealed that the child molesters scored significantly higher than the non‐offender group on the Rationalization of Offending Behavior subscale and the Minimization of Responsibility for Offending subscale, and significantly higher than the non‐child‐molesting sexual offender group on the Minimization of Responsibility for Offending subscale. The authors discuss the meanings of these three types of cognitive distortions and future research issues.